2006
DOI: 10.1128/jvi.00498-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a U L 49-Null Mutant: VP22 of Herpes Simplex Virus Type 1 Facilitates Viral Spread in Cultured Cells and the Mouse Cornea

Abstract: Herpes simplex virus type 1 (HSV-1) virions, like those of all herpesviruses, contain a proteinaceous layer termed the tegument that lies between the nucleocapsid and viral envelope. The HSV-1 tegument is composed of at least 20 different viral proteins of various stoichiometries. VP22, the product of the U L 49 gene, is one of the most abundant tegument proteins and is conserved among the alphaherpesviruses. Although a number of interesting biological properties have been attributed to VP22, its role in HSV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 42 publications
6
88
1
1
Order By: Relevance
“…Unfortunately, this analysis has a major technical caveat. The Bac-ΔVP22 virus is exquisitely sensitive to the acquisition of second site mutations and absolutely must be grown on complementing V49 cells { (Duffy et al, 2006) and data not shown}. Therefore, the Bac-ΔVP22 used in our studies possesses virion-derived VP22.…”
Section: Vp22 Targets Nucleolinmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, this analysis has a major technical caveat. The Bac-ΔVP22 virus is exquisitely sensitive to the acquisition of second site mutations and absolutely must be grown on complementing V49 cells { (Duffy et al, 2006) and data not shown}. Therefore, the Bac-ΔVP22 used in our studies possesses virion-derived VP22.…”
Section: Vp22 Targets Nucleolinmentioning
confidence: 99%
“…HSV-1(Bac-ΔVP22) virus is a VP22-null mutant and HSV-1 (Bac-ΔVP22Repair) virus has the VP22 gene (U L 49) engineered back in (Duffy et al, 2006). All Bac-ΔVP22 stocks were grown on V49 cells, as described (Duffy et al, 2006). To obtain virus stocks, subconfluent monolayer Vero cells (~ 3 × 10 6 cells) were inoculated at a multiplicity of infection (MOI) of 0.01 for 2 hours at 37°C in 199V (Life Technologies) supplemented with 1% newborn calf serum or 2% newborn calf serum.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies with a U L 49-null virus showed that the absence of VP22 results in reduced plaque size and a nearly global shutoff protein synthesis at late times in infection (7,8). Interestingly, passage of the U L 49-null virus on noncomplementing cells led to a rescue of the small plaque phenotype thought to be the result of a secondary, compensatory mutation (7). Further work by other investigators showed that U L 49 mutants propagated on noncomplementing cells frequently acquire secondary mutations in the U L 41 gene.…”
mentioning
confidence: 99%